446 Healthy nightlife: eliminate risk, promote protective factors & city resilience (Coimbra, Portugal). (1st September 2016) - Redondo, João; Mendes, Fernando; Fonseca, Isabel; Alves, Jorge; Anjos, Paulo; Brito, Irma; Armindo, Henrique; Monteiro, António; Diogo, Laura; Baptista, Cristina; Simões, Paulo; Sola, Filipa; et al.
Abstract : Background: Coimbra is certainly among the Portuguese university cities with more nightlife-oriented towards students. The CPTTP and IREFREA–Portugal, are investing, in partnership with other organisations of our city (Health, Education, Security Forces, Municipality, Others sectors) in primary, secondary, and tertiary prevention in nightlife settings. This initiative aims to contribute: to identify and eliminate the risk factors associated with (potentially) traumatic situations (intentional and unintentional); to identify and enhance protective factors; to strengthen community resilience. Description of the problem: Recreation nightlife plays an important role in students' lives but also has an intrinsic association to a multitude of risk factors in areas such as sexuality, violence, alcohol and other substances and road driving. According to a survey conducted by IREFREA in Coimbra, in 2014 (sample: 253 men and 184 women, aged between 16 and 43 years old) many of the night goers report that "today" there is more violence and aggression in the night life (60%), more alcohol intoxication (70%) and higher consumption of illegal drugs (43%). 17.6% reported having had road accidents, 21.4% have been hurt by these and 16.9% have had problems with the police. It is also too high a% of individuals who reported having had sex under the influence of alcohol (64.8%). Results: More participation, interaction and cooperation between network members; more investment on prevention and investigation; more production and exchange of content; more accession of new "actors" and more interactivity and connectivity. Conclusions: Adopting the ecological model, approaching nightlife in a public health perspective, organising care in a multidisciplinary, multisectoral network has contributed to the promotion of more involvement of the "city" aiming the safety and well-being of their citizens.